Penerapan Kurikulum Merdeka Belajar Pada Pembelajaran Bahasa Arab Kelas VIII Mtss Darul Huda Bandar Lampung - Najah, Zughrofiyatun; Hkmaya, Nesa; Erlina (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2025)
This research aims to find out the process of implementing the Independent curriculum,as well as the obstacles, and the impact of implementing the Independetn learning curriculum on Arabic Language Learning at Mtss Darul huda Bandar Lampung.This Independent learning curriculum will be implemented in 2022 at Mtss Darul Huda Bandar Lampung in grade VIII and IX,Curricul is basic guideline in the learning process,where this curriculum determines the success of educational goals.This Independent learning curriculum is in implemented due to a decrease in stiudent learning motivation due to the spread of the covid 19 virus,so that learning must be based online.The methodology in this research uses qualitative descriptions,this research uses data analysis techniques using the miles and Huberman models which have 4 Rare,Namely, data collection,data reduction,data presentation,and drawing conclusions the data obtained was based on observation,namely interviews and documentation,in the learning process,teacher use learning tools called TP,CP,and ATP.The main obstale faced is a lack of knowledge about the new curriculum system and senior teachers who experience difficulties due to outdated teaching habits.The impact specifically learning Arabic for class VII at this scholl,is not much different from the situation when this curriculum was not yet implemented.